ElderCrits as a Building Framework for Black‑Indigenous Peoples’ Decolonizing Solidarities - Dei, George; Adjei, Paul (Canadian Social Work Review / Revue canadienne de service social, 2024)
This paper explores possible sites for critical anti- and decolonial solidarity-building between the Black communities and the Indigenous Peoples in Canada. We leverage African Elders Critical Teachings (ElderCrits) as a discursive framework to conceptualize the interdependence required for a decolonizing solidarity work between Black and Indigenous People, and to expose how white supremacy and colonialism are maintained overtly and covertly in everyday social relations to implicate Black and Indigenous Peoples’ lives in Canada. We conceptualize ElderCrits as bodies of knowledge emerging from the shared voices, experiences, history, cultures, and viewpoints of Indigenous Elders of Africa and Turtle Island over generations because of sustained attachments to the land, culture, and nature. ElderCrits are knowledge grounded in an Indigenous person as a subject knower. ElderCrits are bodies of knowledge that are treasured and held in highest esteem by community members, and they often inform, shape, guide, organize, and regulate how community members uphold the promise of a better future. Such knowledges speak of society, nature, and culture interface, and serve as teachings that guide social behavior and action in Indigenous communities. They are appropriately termed the local cultural resource knowledge of Indigenous Elders. We draw on ElderCrits to nurture a decolonizing solidarity between Black Peoples and Indigenous Peoples in Canada to incite a resistance politics that flees and abandons the carceral projects (Harney & Moten, 2013) of anti-Black and anti-Indigenous racism without leaving out the possibilities of creating new futurities based on inclusive, fair, and equitable relations.